Metagenomic analysis of potential pathogens from blood donors in Guangzhou, China. Issue 1 (17th December 2019) - Gao, Lei; Rong, Xia; He, Miao; Zhang, Ling; Li, Tingting; Wang, Wenjing; Candotti, Daniel; Allain, Jean‐Pierre; Fu, Yongshui; Li, Chengyao
Abstract: Objectives: This study aimed to identify the emerging/reemerging pathogens in blood donation samples. Background: A metagenomic analysis has previously been used to look for pathogens but in this study, the relationship with aminotransferase (ALT) is described. Methods/Materials: Excluding samples reactive to hepatitis B virus, hepatitis C virus, human immunodeficiency syndrome virus or syphilis and plasma samples were stratified into three groups of ALT levels (IU/L): A ≤ 50, B 51 to 69 and C ≥ 70, respectively. Each group was mixed in a pool of 100 samples, from which DNA and cDNA libraries were established for next generation sequencing and analysis. Pathogens of interest were identified by immunoassays, nested‐polymerase chain reaction, phylogenetic analysis and pathogen detection in follow‐up donors. Results: Several new or reemerging transfusion‐transmitted pathogens were identified; Streptococcus suis, Babesia species and Toxoplasma gondii were found in the three ALT groups, Epstein‐Barr virus (EBV) only in group C. Ten S. suis nucleic acid positive samples were detected, all closely phylogenetically related to reference strains. A donor in group A carried both S. suis genome and specific IgM in follow‐up samples. This strain was identified as nontoxic S. suis . Five samples contained a short fragment of Babesia species SpeI‐AvaI gene, while T. gondii was identified in 20 samples as a short fragment of 18S rDNA gene. In group C, two samples contained EBV genome. Conclusions: Blood donations that contained S. suis, Babesia species and T. gondii sequences might represent potential transfusion risks. EBV, a potential cause of elevated ALT, was detected. Metagenomic analysis might be a useful technology for monitoring blood safety.